1991
DOI: 10.1002/ptr.2650050510
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing effect of calaguala on the prevention of rejection on skin transplants in mice

Abstract: L.-0. Lindbom and W. RolfsenKabi Pharmacia AB, S-751 82 Uppsala, Sweden Calaguala, an extract from the fern Polypodium decumanum, has been used to treat psoriasis and other immunologically related disorders. In order to elucidate whether an immunosuppressive mechanism could explain the clinical effect, Calaguala was studied in a skin model of allograft rejection in mice. Calaguala significantly prolonged the allograft survival compared with untreated transplanted mice. The results indicate that Calaguala exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…leucotornos extract is a hydroalcoholic extract containing a saponin formed by a ketosteroid and deoxyhexose with little published information on its composition and structure of active ingredient(s) (19). The extract has been shown to exhibit immunomodulating activities in vitro and in vivo, exemplified by an increase in number of lymphocytes CD8+ (20), a prolongation of the survival of skin allografts in mice (21), suppression of effector and memory T-cells and increase of NK activity, modulation of brain levels of some cytokines in rats (22), suppression of proliferative response to exogenous r-IL-2 and antiCD3 mononuclear antibodies (23), and inhibition of both the release of elastase in human neutrophils induced by platelet activating factor (PAF), and the biosynthesis of PAF (24). In recent years, Z?…”
Section: Polypodium {Eucotornosmentioning
confidence: 99%
“…leucotornos extract is a hydroalcoholic extract containing a saponin formed by a ketosteroid and deoxyhexose with little published information on its composition and structure of active ingredient(s) (19). The extract has been shown to exhibit immunomodulating activities in vitro and in vivo, exemplified by an increase in number of lymphocytes CD8+ (20), a prolongation of the survival of skin allografts in mice (21), suppression of effector and memory T-cells and increase of NK activity, modulation of brain levels of some cytokines in rats (22), suppression of proliferative response to exogenous r-IL-2 and antiCD3 mononuclear antibodies (23), and inhibition of both the release of elastase in human neutrophils induced by platelet activating factor (PAF), and the biosynthesis of PAF (24). In recent years, Z?…”
Section: Polypodium {Eucotornosmentioning
confidence: 99%
“…The first natural product evaluated in this study was an extract from Polypodium leucotomos (PL) that has been used in Central America for the treatment of several phlogistic disorders, including skin-associated inflammatory problems (psoriasis, atopic dermatitis) (22,23). PL has shown an antioxidant action in several studies (24).…”
Section: Introductionmentioning
confidence: 99%
“…In order to study whether an immunosuppressive activity could explain the observed effect of Calaguala in the treatment of psoriasis, a skin model of allograft rejection in mice was used. A methanolic extract of the leaves of the fern significantly prolonged the allograft survival compared with untreated transplanted mice and in the same order as the immunosuppressant drug cyclosporin A did (Tuominen et al ., ).…”
Section: Bioassay‐guided Isolationmentioning
confidence: 97%